Evaluasi Penggunaan Material Bekisting Kayu Pada Proyek Pembangunan Gudang Penyimpanan Limbah PT. Ansori Jaya - Putra, Alfandias Seysna; Almahdi , Muhammad Arief; Halmar, Rifqi Fauzan; Lesatri, Indah Fuzy; Ramadhan, Muhamad Reza Akbar (JURNAL TEKNIK SIPIL, 2023)
The building has various elements such as subgrade, foundation, sloof, beam, column, wall, floor, and roof. In the process of working on building elements, a budget plan (RAB), materials, draft drawings, and human resources are needed. Material is one of the important components in construction projects. The success or failure of a building construction project, one of which is determined by the quality of material management in supporting the success of a project. The research location is in the construction of the temporary waste storage warehouse of PT Ansori Jaya. The research was conducted by analyzing the RAB, Analysis of Unit Price of Work, and Material Purchase Report. Based on the research, class III wood formwork material purchased by the contractor was 46.71 m3 and used as much as 18.18 m3. Class II wood purchased by the contractor was 15, 23 m3, and used as much as 7.32 m3. For Plywood the contractor bought as much as 830 sheets and used as many as 160 sheets. As for galam wood, the contractor bought 608 pcs, and was used entirely. All materials used for floor plate work and 3rd-floor beams.